Electronic Forgery As a Manifestation of Digital Corruption - Khiari , Rayane; Selmani, Hayette (Journal of Legal Studies and Researches, 2026)
This article examines the offense of cyber forgery as a major threat in the field of digital corruption. Cyber forgery demonstrates how technology can be used for illegal purposes, such as tampering with digital documents, hacking into systems, and falsifying data for illicit gain. These actions demonstrate that cyber forgery is not just a cyber crime, but an integral part of digital corruption, negatively impacting society and the economy as a whole. One of the main effects of cyber fraud is that it undermines trust in digital systems. This type of crime contributes to digital corruption by manipulating electronic processes and falsifying official documents. Moreover, cyber forgery contributes to hampering efforts to achieve transparency and integrity in various institutions, whether governmental or private. By analyzing the impact of this crime, this article seeks to clarify the complex dimensions of cyber forgery and the importance of developing effective strategies to combat it and enhance digital security.